DO OIL PRICE SHOCK, AND OTHER MACROECONOMIC VARIABLES AFFECT THE STOCK MARKET: A STUDY OF THE SAUDI STOCK MARKET - Alam, Naushad (Humanities & Social Sciences Reviews, 2020)
Purpose of the study: This work aims to find the type of relationship amongst the chosen variables, inflation (INF), short-term interest rate (SIR), money supply (M.S.) and crude oil price (COP) and oil price shocks represented by DUMMY respectively on the capital market of Saudi Arabia. It will also throw insight to policymaker to find factors which influence the capital market of Saudi Arabia and to take remedial measures to boost investment in the country. Research Methodology: The relationships amongst the Saudi security market, the oil price shock, and the selected macroeconomic variables as mentioned above are determined using the Johansen test of co-integration, the vector error correction model, and the Wald test. The research employs the time series data for a period of 2009to 2016, for the study. Findings: The results show a long-run equilibrium relationship between the Saudi stock market and the selected variables for the study. The study shows a positive association between the money supply and the stock market, but inflation, short-term interest rate, and crude oil price, the result indicates a negative relationship. Implications: The present study can have implications for the policymaker to take corrective measures for better performance of the stock market by controlling inflation and regulating the short-term interest rate.As the findings indicate that they have a negative relationship with TASI. This paper will also help the policymaker in identifying the real cause for the decline in the value of the stock price. A good performing stock market means better economic growth and overall economic development. To diversify the economy to have an alternative to the oil-driven economy to a more balanced economy by promoting other sectors like manufacturing and tourism. Novelty/Originality of this study: The literature review confirms that all work of oil price shock is related to its effect on the security market return. This work is different from the other study as it includes macroeconomic variables in the study, together with the oil price shocks. The study is unique from other studies as it is broader in approach, by including more variables than earlier studies which mostly included the oil price shocks and its impact on the stock market. There is no work done to investigate the joint effect of macroeconomic variables and oil price shocks on the Saudi stock market.